analisis pengaruh dana pihak ketiga, non performing financing, financing to deposit rasio terhadap volume pembiayaan pada bank umum syariah di indonesia periode 2011-2014. - Hastuti, Lina, Drs. Atwal ArifinM.Si., Ak (2016)
The purpose of the study was to determine the influence of Third Party Fund (TPF), Non Performing Financial (NPF), Financial to Deposit Ratio (FDR) the volume of financing. The data used are quarterly financial statements Islamic commercial bank published on the website each sample Sharia Commercial Bank in Indonesia for period 2011-2014. This research method is quantitative. By using the technique of multiple regression test with the help of computers using SPSS 21.0. with a significant test of simultaneous (statistical of F), significant test of individual parameters (statistical test t), test the coefficient of determination R2. Based on research results in regression models can be conclued that (TPF) and FDR variables that significantly influence the volume of financing. NPF whereas no significant effect on the volume of the volume of financing. Keywords: Third Party Fund, Non Performing Financial, Financial to Deposit Ratio and volume of financing.